8x+6(-2x-7)=-41-5x

Simple and best practice solution for 8x+6(-2x-7)=-41-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+6(-2x-7)=-41-5x equation:


Simplifying
8x + 6(-2x + -7) = -41 + -5x

Reorder the terms:
8x + 6(-7 + -2x) = -41 + -5x
8x + (-7 * 6 + -2x * 6) = -41 + -5x
8x + (-42 + -12x) = -41 + -5x

Reorder the terms:
-42 + 8x + -12x = -41 + -5x

Combine like terms: 8x + -12x = -4x
-42 + -4x = -41 + -5x

Solving
-42 + -4x = -41 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-42 + -4x + 5x = -41 + -5x + 5x

Combine like terms: -4x + 5x = 1x
-42 + 1x = -41 + -5x + 5x

Combine like terms: -5x + 5x = 0
-42 + 1x = -41 + 0
-42 + 1x = -41

Add '42' to each side of the equation.
-42 + 42 + 1x = -41 + 42

Combine like terms: -42 + 42 = 0
0 + 1x = -41 + 42
1x = -41 + 42

Combine like terms: -41 + 42 = 1
1x = 1

Divide each side by '1'.
x = 1

Simplifying
x = 1

See similar equations:

| (x-8)(5x+9)=0 | | -43-3x=7-9x | | (x+2)(x+2)=0.25 | | 3x^2y^4-81x^2y=x | | 10x-3=4x-5 | | 2*3x+3+3x+5=99 | | 2x+47=3x+14 | | 4x+8=89-56 | | x^2+4x+3.75=0 | | 8x^3-240x-9=0 | | 15x+60=0 | | 20x^2-45= | | 960/3= | | 24x^3+27x^2+7x+7= | | 24x^3+27x^2+7+7= | | 24x^3+27x^2+7x=7 | | x^2+x+0.25=0 | | 130-3x=24x-16 | | (8x+9)(3x^2+7x+7)= | | 3x+10=86-9x | | h=13gh | | c=b+bcd | | x^2-8x+16=2x+16 | | 6w^2+31w+40=0 | | 5(x-4)=4-3x | | x+2+3+3+3-3=51 | | 2ln(x+9)-8lnx= | | lne^3x= | | 9(2y-9)-(8y+5)= | | 13+18x=535 | | 12+20x=132 | | (5x+1)(4x^2+2x+3)= |

Equations solver categories